Urban Development and Business Growth: A Case Study of Kabale Municipality. - Natukwatsa, Doreen (Kabale University, 2023)
The purpose of this research was to examine the effect of urbanization on business growth in Uganda. A case study of Kabale municipality. The study was guided by objectives namely to examine the effect of market availability on business growth, to find out the effect of technology on business growth, and to examine the improved infrastructure on business growth in Uganda. The study used 88 respondents and a sample size. The study used a descriptive research design based on qualitative and quantitative approaches in order to get a better analysis of the study. Both primary and secondary data collection tools were used with their relevant tools like questionnaires and interview guides in order to come up with the required data. In the findings, it was established that marketing and advertisement can serve to inform customers about the new product. Due to the market presence of products, customers will informed of new products whenever a new product is produced from the business, factory or industry. From the findings, businesses have advanced internal communications quite a bit as well, making it possible for employees at many companies to work from home throughout the coronavirus pandemic. Much data is stored electronically now, making it easier for retrieval when the information is needed hence business growth. Some respondents agreed that businesses are able to produce and deliver more goods and services to customers where they are and this will not only increase selling but also profits which will increase business growth. Some respondents mentioned that high-quality infrastructure that is sustainable increases business activities, creates new employment, narrows income disparities, and empowers gender participation. According to the questionnaire also, infrastructure is relevant to trade facilitation, particularly in minimizing trade costs and further enhancing competitiveness. The study concludes that Urbanization is a complex issue that must be assessed not only in terms of urbanization speed or effects of business growth. The forward conditions of urbanization can be analyzed through market availability that will help to make businesses sell their produce and therefore governments need to focus on creating an environment that supports market availability for businesses to grow in Kabale district. The study recommends that businesses in Uganda should invest much in advertisement and producing quality goods to promote their market availability in their businesses. This will make many customers to know much about their produce and buy more as businesses grow.